Fragile X Syndrome: Prevalence, Treatment, and Prevention in China - Niu, Manman; Han, Ying; Dy, Angel Belle C.; Du, Junbao; Jin, Hongfang; Qin, Jiong; Zhang, Jing; Li, Qinrui; Hagerman, Randi J. (Frontiers in Neurology, 2017)
Fragile X syndrome (FXS) is the most common inherited cause of intellectual disability (ID) and the leading monogenic cause of autism spectrum disorder (ASD). Although FXS has been studied for several decades, there is relatively little basic science or clinical research being performed on FXS in China. Indeed, there is a large gap between China and Western countries in the FXS field. China has a potentially large number of FXS patients. However, many of them are under-diagnosed or even misdiagnosed, and treatments are not always administered in the Chinese population. This review discusses the prevalence, treatment, and prevention of FXS in China to facilitate an understanding of this disease in the Chinese population.